2004
DOI: 10.1002/chir.20031
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric resolution of kielcorin derivatives by HPLC on polysaccharide stationary phases using multimodal elution

Abstract: Analytical HPLC methods using carbamate chiral stationary phases of polysaccharide derivatives were developed for the enantiomeric resolution of five racemic mixtures of xanthonolignoids: rac-trans-kielcorin C, rac-cis-kielcorin C, rac-trans-kielcorin D, rac-trans-isokielcorin D, and rac-trans-kielcorin E. The separations were evaluated with the stationary phases cellulose tris-3,5-dimethylphenylcarbamate, amylose tris-3,5-dimethylphenylcarbamate, amylose tris-(S)-1-phenylethylcarbamate, and amylose tris-3,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The use of these chiral phases has been previously demonstrated on many occasion [28][29][30][31][32][33][34], as in the direct separation of multimilligram quantities of gossypol enantiomers using tris-3,5-dimethylphenylcarbamate cellulose phase on the reversed mode of elution, with efficient recovery for the enantiomers (80%) [35]. Sousa et al [36] also showed the versatility of these polysaccharide phases, under polar organic conditions, in the separation of the xanthonolignoids enantiomers in multimilligram scale.…”
Section: Introductionmentioning
confidence: 92%
“…The use of these chiral phases has been previously demonstrated on many occasion [28][29][30][31][32][33][34], as in the direct separation of multimilligram quantities of gossypol enantiomers using tris-3,5-dimethylphenylcarbamate cellulose phase on the reversed mode of elution, with efficient recovery for the enantiomers (80%) [35]. Sousa et al [36] also showed the versatility of these polysaccharide phases, under polar organic conditions, in the separation of the xanthonolignoids enantiomers in multimilligram scale.…”
Section: Introductionmentioning
confidence: 92%
“…To meet this end, chiral screening technologies have been pursued using either traditional columns (5 μm fully porous particles) [ 49 , 54 , 55 , 56 , 57 , 58 ] or multi-column parallel screening [ 59 ], as well as other advanced technologies for increasing high throughput and efficiency [ 60 , 61 ]. The ultraviolet (UV) detector is still the most used, but chiral detectors based on polarimetry or ECD has become a tendency for e.r.…”
Section: Tutorialmentioning
confidence: 99%
“…They were first introduced back in 1984 [ 65 , 66 ] and since then, a large variety of derivatives of cellulose and amylose coated to silica have been successfully employed [ 67 ]. The polysaccharide-based coated phases are used under normal, reverse, or polar organic elution modes [ 55 , 68 ], however modifiers such as acetone, ethyl acetate, dichloromethane, dimethyl sulfoxide and methyl t -butyl ether cannot be used due to the solubility of the chiral selectors in these solvents [ 68 , 69 ]. To overcome these problems, despite reducing their chiral recognition ability, polysaccharide-based chiral selectors have been immobilized to silica gel as a gain in technology [ 48 , 56 , 67 ].…”
Section: Tutorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Um outro grupo, do Instituto de Química da Universidade Federal de São Carlos, atua no desenvolvimento de novas fases estacionárias quirais e modos de separação e, mais recentemente, em aplicações na análise de fármacos quirais em materiais biológicos. As publicações mais recentes desse grupo [130][131][132][133][134] também atestam sua importante contribuição na análise enantiosseletiva empregando HPLC.…”
Section: Contribuição De Grupos Brasileiros Na Análise Enantiosseletiunclassified